2020
DOI: 10.3390/cancers12082298
|View full text |Cite
|
Sign up to set email alerts
|

AT101 [(-)-Gossypol] Selectively Inhibits MCL1 and Sensitizes Carcinoma to BH3 Mimetics by Inducing and Stabilizing NOXA

Abstract: Anti-apoptotic BCL2 proteins are important targets for cancer therapy as cancers depend on their activity for survival. Direct inhibitors of MCL1 have entered clinical trials, although their efficacy may be limited by toxicity. An alternative approach may be to induce the pro-apoptotic protein NOXA which selectively inhibits MCL1 in cells. Many compounds originally proposed as inhibitors of the BCL2 family were subsequently found to induce the pro-apoptotic protein NOXA through the unfolded protein response. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…It should be noted that although several preclinical data and clinical trials have demonstrated the antitumor effect and the good tolerance of (−)-gossypol, , it has shown only modest clinical efficacy as a single agent with no objective responses. , Therefore, several studies have investigated the combined effects of (−)-gossypol and chemo- or radiotherapy. Zerp et al showed that (−)-gossypol is a potent enhancer of radiation-induced apoptosis in vitro and, importantly, that in vitro radiosensitization was observed at clinically achievable plasma levels . Taken together, these findings provide a rationale to further evaluate the in vivo antitumor efficacy of gossypol, a small-molecule autophagy modulator identified in our study, in combination with currently available anticancer therapies.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that although several preclinical data and clinical trials have demonstrated the antitumor effect and the good tolerance of (−)-gossypol, , it has shown only modest clinical efficacy as a single agent with no objective responses. , Therefore, several studies have investigated the combined effects of (−)-gossypol and chemo- or radiotherapy. Zerp et al showed that (−)-gossypol is a potent enhancer of radiation-induced apoptosis in vitro and, importantly, that in vitro radiosensitization was observed at clinically achievable plasma levels . Taken together, these findings provide a rationale to further evaluate the in vivo antitumor efficacy of gossypol, a small-molecule autophagy modulator identified in our study, in combination with currently available anticancer therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the R(-)-Gossypol enantiomer AT-101, has also been encouragingly reported to reduce invasiveness of rat MLL PC cells [ 176 ] and induce mitophagy in U87MG and U343 glioma cells [ 177 ]. Mechanistically, Gossypol and AT-101 may contribute to cell death by binding and inhibiting Mcl1, resulting in the sensitization of several cell lines to other therapeutics or through it stabilizing NOXA expression, as in gastric, breast and nasopharyngeal cell lines [ 178 , 179 ]. Collectively, racemic Gossypol or its enantiomer are showing good potential as anti -cancer agents which induce cell death through a variety of mechanisms, and in a variety of cell line-based models.…”
Section: Main Textmentioning
confidence: 99%